Vaccines against Theileria parva - Morzaria, S.P.; Nene, Vishvanath M.; Bishop, Richard P.; Musoke, A.J. (Wiley, 2000)
Bovine theileriosis caused by Theileria parva continues to be a major economic problem in many parts of Eastern, Southern, and Central Africa. Due to the unsustainable nature or the present control method-using toxic acaricides to kill ticks - alternative control methods are being sought. Live vaccines are being used in many countries in the region. 'These vaccines are based on the infective sporozoite stage of the parasite. Sporozoites are inoculated in cattle with simultaneous administration of a long-acting formulation of oxytetracycline. These vaccines are poorly adopted in the region, mainly because of problems associated with the use of live parasites. An experimental recombinant vaccine based on a sporozoite surface antigen (p67) has been developed. Immunization with this antigen induces neutralizing antibodies and, under laboratory conditions, this technique protects approximately 70% of the immunized cattle to a defined needle challenge. The efficacy of the vaccine is currently being evaluated under field challenge in Kenya. Since a vaccine based on a single antigen may not be sustainable under field conditions, a search for schizont antigens that induce protective cell-mediated immune responses continues. It is expected that the ultimate vaccine against theileriosis will incorporate a mixture of several antigens derived from both sporozoite and schizont stages, contributing to robust immunity.